Growth response of itchgrass (Rottboellia cochinchinensis) to water stress - Chauhan, Bhagirath S. (Cambridge University Press, 2013)
Greenhouse studies were conducted to evaluate the growth response of itchgrass to water stress. Itchgrass plants produced the greatest aboveground biomass and seeds at 75% of field capacity and these parameters at 50 and 100% of field capacity were similar. With further increase in water stress, seed production was sharply reduced, but itchgrass was still able to produce an average of 63 and 9 seeds plant−1at 25 and 12.5% of field capacity, respectively. Itchgrass plants responded to increasing water stress with increased leaf weight ratio; it was 2.5 times greater at 12.5% of field capacity than at 100% of field capacity. In another study, compared with daily irrigation, intervals of 9 d between irrigations reduced aboveground biomass of itchgrass by 27% and 12-d intervals reduced aboveground biomass by 67%. Compared with the daily irrigation regime, itchgrass seed production was reduced by 61% at intervals of 12 d between irrigations; however, the weed plants produced a considerable number of seeds (153 seeds plant−1) at the 12-d intervals. The ability of itchgrass to produce biomass and seeds under water stressed conditions necessitates strategies that minimize weed survival while maximizing irrigation efficiency for the crop at the same time.